Optimal formulations of local foods to achieve nutritional adequacy for 6-23-month-old Yemeni children - Nabil Q. M. Al-Hajj; Abdullah Almikhlafy; Mansour Ghalib; Methaq Algabr; Sallah A. Al-Hashedi (Aden University, 2022)
The study formulated six complementary food mixtures from locally available Yemeni crops including teff flour, rice, sorghum, wheat, sweet potatoes and lentils, with roasting applied to improve nutritional quality and sensory characteristics. Protein, fat, carbohydrate and mineral contents were assessed and trained panelists evaluated acceptability using a hedonic scale, with the aim of identifying affordable local foods that could help improve nutritional adequacy among Yemeni children aged 6-23 months.